LAW ENFORCEMENT ON PERPETRATORS OF FUEL OIL AND GAS COUNTERFEITING IN BANGILAN, TUBAN - Slamet; Subekti; Soekorini, Noenik (jfpublisher, 2023)
The purpose of this research is to analyze the implementation of law enforcement of perpetrators and analyze efforts to overcome perpetrators of criminal acts of counterfeiting fuel oil and gas in Bangilan Village, Bangilan Kecaatan, Tuban. This research is included in sociological juridical research. The legal sociological approach is a science from the development of legal science and can be observed by studying social phenomena that have legal aspects in society. The results of this research indicated that the implementation of law enforcement perpetrators of criminal acts of counterfeiting fuel oil and gas in Bangilan Village, Bangilan District, Tuban, the investigator concluded that the actions committed by the suspect Soniawan prasetio were proven to have violated Article 54 and Article 53 of the Law of the Republic of Indonesia No. 22/2001 concerning Oil and Gas, as amended by Law of the Republic of Indonesia No. 11/2020 concerning Copyright Work. The efforts of the East Java Regional Police in overcoming the criminal act of counterfeiting diesel fuel (BBM) are carried out with countermeasures in the form of pre-emptive efforts, preventive efforts and repressive efforts.